An Evidence-Informed Response to Slum Settlements : A Learning Note - World Bank (Washington, DC, 2013)
This learning note prepares policymakers to engage with their technical experts and staff in designing and implementing an evidence-informed response to the challenges of existing and future slum settlements. To that end, the note discusses a set of indicators and data analysis techniques needed in the identification and characterization of slums as well as relevant lessons and examples. In addition, the noted discusses the data requirements of various policy responses.